Respuesta :
We determine the answers to these items by substituting the values before performing the operation.
1) (f + g)(2) f(2) = 2(2) + 3 = 7 g(2) = 2² - 1 = 3 (f + g)(2) = 7 + 3 = 10 (Answer for 1 is B)
2) (f - g)(4) f(4) = 2(4) + 3 = 11 g(4) = 4² - 1 = 15 (f - g)(4) = 11 - 15 = -4 (Answer for 2 is A)
3) (f ÷ g)(2) (f x g)(1)
We already have the values of f(2) and g(2) above (in number 1) f(1) = 2(1) + 3 = 5 g(1) = 1² - 1 = 0
The answer to this item is zero because any number multiplied to zero is zero. Letter C.
1) (f + g)(2) f(2) = 2(2) + 3 = 7 g(2) = 2² - 1 = 3 (f + g)(2) = 7 + 3 = 10 (Answer for 1 is B)
2) (f - g)(4) f(4) = 2(4) + 3 = 11 g(4) = 4² - 1 = 15 (f - g)(4) = 11 - 15 = -4 (Answer for 2 is A)
3) (f ÷ g)(2) (f x g)(1)
We already have the values of f(2) and g(2) above (in number 1) f(1) = 2(1) + 3 = 5 g(1) = 1² - 1 = 0
The answer to this item is zero because any number multiplied to zero is zero. Letter C.
Answer:
[tex](f+g)(2)=10[/tex]
[tex](f-g)(4)=-4[/tex]
(f÷ g)(2)=[tex]\frac{7}{3}[/tex]
[tex](f*g)(1)=0[/tex]
Step-by-step explanation:
[tex]f(x) = 2x + 3[/tex] and [tex]g(x) = x^2 - 1[/tex]
Lets find f(2) , f(4) , g(4) and g(2)
[tex]f(x) = 2x + 3[/tex
[tex]f(2) = 2(2) + 3=7[/tex]
[tex]f(4) = 2(4) + 3=11[/tex]
[tex]f(1) = 2(1) + 3=5[/tex]
[tex]g(x) = x^2 - 1[/tex]
[tex]g(2) = 2^2 - 1=3[/tex]
[tex]g(4) = 4^2 - 1=15[/tex]
[tex]g(1) = 1^2 - 1=0[/tex]
LEts find (f+g)(2)
[tex](f+g)(2)= f(2) + g(2)=7+3=10[/tex]
[tex](f-g)(4)= f(4) - g(4)=11-15=-4[/tex]
(f÷ g)(2)=[tex]\frac{f(2)}{g(2)} =\frac{7}{3}[/tex]
[tex](f*g)(1)= f(1) * g(1)=5*0=0[/tex]